Education in the age of the information superhighway: An investigation into initial teacher training in Canada - Illingworth, Martin (Canadian Journal of Education/Revue canadienne de l’éducation, 2012)
This article discusses particular aspects of current Canadian teacher training that seem healthy practice to an experienced school-teacher from the United Kingdom. With the UK government increasingly interested, some would say determined, in moving the funding of initial teacher training away from universities and to schools, my visit to Canada, and specifically to Ontario Institute for Studies in Education at The University of Toronto, focuses on those practices that appear supportive of deep learning for beginning teachers in helping them to develop their own sense of the purposes of education and ways in which they might become agents of change. Keywords : comparative initial teacher training programmes, social justice, Ontario Institute for Studies in Education, United Kingdom and Canada